Lower limit of normality and clinical relevance of left ventricular early diastolic strain rate for the detection of left ventricular diastolic dysfunction. (3rd August 2017) - Morris, Daniel A; Takeuchi, Masaaki; Nakatani, Satoshi; Otsuji, Yutaka; Belyavskiy, Evgeny; Aravind Kumar, Radhakrishnan; Frydas, Athanasios; Kropf, Martin; Kraft, Robin; Marquez, Esteban; Osmanoglou, Engin; Krisper, Maximilian; et al.
Abstract: Aims: The aim of the present study was to determine the lower limit of normality and the clinical relevance of left ventricular (LV) early diastolic strain rate (LVSRe) for the detection of LV diastolic dysfunction (LVDD). Methods and results: Using 2D speckle-tracking echocardiography, we analysed 377 healthy subjects and 475 patients with risk for LVDD with preserved LV ejection fraction (LVEF). The normal range of LVSRe analysing the healthy subjects was 1.56 ± 0.28 s −1, with a lower limit of normality at 1.00 s −1 . Using this cut-off, LVSRe was able to detect high rates of LV diastolic alterations (rate 71.1%), which was significantly better than using indirect diastolic parameters such as left atrial volume index (LAVI) and tricuspid regurgitation velocity (TR) (rates 22.9% and 9.1%) and similar to annular mitral parameters such as lateral and septal e ʹ velocity (rates 70.9% and 72.4%). In line, adding LVSRe to the current evaluation of LVDD increased significantly the rate of detection of LVDD (absolute rate of increase 18.9%; rate of detection of LVDD: from 14.3% to 33.2%, P < 0.01). Regarding the clinical relevance of LVSRe, patients with abnormal LVSRe (i.e. <1.00 s −1 ) had significantly worse New York Heart Association functional class and symptomatic status than those with normal LVSRe. In addition, in a retrospective post hoc analysis, we found that an abnormal LVSRe had a significant association with the risk of heart failure hospitalization at 2 years (odds ratio 5.0, 95% confidence interval 1.3–18.4), which was better than using conventional diastolic parameters such as septal and lateral e ʹ velocity, LAVI and TR velocity. Conclusion: The findings from this multicentre study provide important data regarding the normal range of LVSRe and highlight the potential clinical relevance of using this new diastolic parameter in the detection of LVDD in patients with preserved LVEF.